(untitled) (Journal Of Educational and Psychological Researches, 2025)
This study aims to detect the differences in family safety perception (FSP), school safety perception (SSP), psychological capital (PC), and psychological well-being (PWB) in terms of gender and studying stage; verify the good fitness of the structural model of relationships between FSP, SSP, PC, and PWB; and test the mediating role of SSP and PC. The study adopted the descriptive (correlational-comparative) approach. The sample consisted of 1511 male and female students in the Kingdom of Saudi Arabia (697 males, 814 females) aged between 13-18 years, including 866 male and female students in high school and 645 male and female students in middle school. The FSP, SSP, PC, and PWB scales were applied to the study sample. The results showed strong evidence to accept the null hypothesis regarding gender differences; however, strong evidence was found to take the alternative hypothesis regarding the differences between middle and high school students, as the differences in favor of high school students in FSP, SSP, PC, and PWB. The results also found statistically significant (P < 0.05) direct and indirect effects of FS, SS, and PC on PWB, a partial, complementary, single mediating role for PC in the relationship between FS and SS with PWB, and a multiple, complementary, mediating role for SSP and PC in the relationship between FSP and PWB, as the total effects of each of FSP (0.945), SSP (0.349), and PC (0.644) on PWB. In light of these results, the study recommended integrating PWB interventions into counseling services for students.